How to Hedge against Inflation Risk in Vietnam - Nguyen Thi Thanh Binh (Economies, 2023)
Vietnam has experienced galloping inflation and faced serious dollarization since its reform. To effectively control inflation for promoting price stability, it is necessary to find efficacious leading indicators and a hedging mechanism. Using monthly data over the period from January 1997 to June 2020, this study finds the predictive power and hedge effectiveness of both gold and the US dollar on inflation in the long-run and short-run within the asymmetric framework. Especially, the response of inflation to the shocks of gold price and the US dollar is quick and decisive, disclosing the sensitivity of inflation to these two variables.